Dynamics and Formation of Obscuring Tori in AGNs - Bannikova, Elena Yu.; Sergeyev, Alexey V. (Frontiers in Astronomy and Space Sciences, 2017)
We considered the evolution of a self-gravitating clumpy torus in the gravitational field of the central mass of an active galactic nucleus (AGN) in the framework of the N-body problem. The initial conditions take into account winds with different opening angles. Results of our N-body simulations show that the clouds moving on orbits with a spread in inclinations and eccentricities form a toroidal region. The velocity of the clouds at the inner boundary of the torus is lower than in a disk model that can explain the observed rotation curves. We discuss the scenario of torus formation related with the beginning of the AGN stage.